The role of scattering -limited and ballistic transport in performance evaluation of nano-CMOS circuit - Vijay Kumar Arora, author; International Workshop on Electron Dervices & Semiconductor Technology (2nd : 2009 : India) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL